A million dollar measles outbreak: epidemiology, risk factors, and a selective revaccination strategy. - Robertson, S E (1992)
Between February 8 and April 4, 1986, an outbreak of measles occurred in the State of Arkansas. A total of 489 suspected measles cases were reported from 53 counties; 86 schools statewide reported suspected measles cases. There were 284 cases confirmed in 18 counties; 23.6 percent among students in one university and 41.2 percent among students in kindergarten through 12th grade in 32 schools. An epidemiologic investigation was carried out to evaluate risk factors for vaccine failure and to assess the effectiveness of a selective revaccination strategy in the outbreak setting. A cohort study conducted at a junior high school showed that, compared with students vaccinated against measles at ages 15 months or older, those vaccinated at ages 12-14 months had a three-fold increased risk of measles (relative risk 3.2, 95 percent confidence interval 1.5, 6.9). For schools reporting measles, the Arkansas Department of Health and the Department of Education jointly required reimmunization of students vaccinated at ages younger than 15 months and the exclusion of students not vaccinated at ages 15 months or older until they were vaccinated or until 2 weeks after the last rash onset. To implement these recommendations, more than 100,000 doses of combined measles-mumps-rubella vaccine were distributed at a cost greater than $1 million.